MARJIN PEMASARAN DAN RESIKO PEDAGANG: KASUS PENGEMBANGAN RUMPUT LAUT DI PROPINSI GORONTALO - ARMEN ZULHAM (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2008)
Intensive seaweed development program occured during fisheries revitalitation programrealesed by government. The development of this commodity triggred by highly demand ofseaweed raw material and it’s derivative in domestic and export markets. This article writebased on the RRA survey technique on marketing marjin and trade risk face by traders onseaweed trade in Gorontalo. Responden interviewed covered the stakeholders involve inseaweed business in Gorontalo. The primary data were used to analysed the marketing marjinand trader’s risk of seaweed in Gorontalo. The traders who involved in seaweed businessassume to be risk preference, due to profit oriented as long as risk oriented. The researchfinding indicated: the price sharing recive by each stakeholder compared the retail price inSurabaya and Manado quite preferable. Asymetric price information not occured among tradelevels. Marketing marjin at each level and total marjin relatively low. This informationindicated the marketing cost of seaweed more absorbed for transportation cost. As a riskpreference, the trader who sold the seaweed to Manado face highly risk compared to theirpartner who sold sea weed to Surabaya, respectively. The active involvement of governmentin seaweed business need the proper planning and strategy to ignore the disappearing target.